Day 1 Tue, December 06, 2016 2016
DOI: 10.2118/184118-ms
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Steam Generation A New Technology Application for Heavy Oil Production

Abstract: The recovery of unconventional oil such as heavy oil is receiving great interest as the world oil demand is increasing along with relatively high oil prices. Producing such high viscosity oil is complex and challenging, which usually require thermal techniques. Thermal recovery methods are widely used to recover the heavy oil and bitumen basically by thermally reducing oil viscosity, improving the mobility ratio and enhancing the heavy oil displacement. In response to the recent effort of levera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…Solutions of ammonium chloride (NH 4 Cl) and sodium nitrite (NaNO 2 ) were used as thermochemical fluids, and the chemical reaction was triggered using an acid. The chemical reaction during thermochemical injection can be represented by Equation (1) [18,26,27]:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Solutions of ammonium chloride (NH 4 Cl) and sodium nitrite (NaNO 2 ) were used as thermochemical fluids, and the chemical reaction was triggered using an acid. The chemical reaction during thermochemical injection can be represented by Equation (1) [18,26,27]:…”
Section: Methodsmentioning
confidence: 99%
“…Injection of thermochemical fluids into gas condensate reservoirs can result in enhancing hydrocarbon production utilizing several mechanisms. The injected chemicals are able to generate a significant amount of heat and pressure at the reservoir condition; the generated heat and pressure can reach to 644.3 K and 34.5 MPa [18,26]. The induced heat and pressure change the behavior of the condensate liquid.…”
Section: Gas Production Improvementmentioning
confidence: 99%
See 2 more Smart Citations
“…Through their experiments, they have found that thermochemical reduces the rock strength significantly which reduces the pumping pressure in a typical hydraulic fracturing job. Al-Nakhli et al [39] experimentally investigate the increase in production from heavy oil due to in situ generation of steam by applying new thermochemical technology. Al-Nakhli et al [40][41][42] also investigated the effect of thermochemical on different rock samples.…”
Section: Literature Reviewmentioning
confidence: 99%